Energy consumption in open and enclosed layout of shopping malls in Malaysia - Yaman, Rostam; Yaziz, Nur Suzziana; Ismail, Farrah Zuhaira; Ahmad, Noraini (Construction Research Institute of Malaysia (CREAM), 2022)
Shopping mall requires a huge amount of energy, in terms of embodied and operational energy needed to operate. This research aim is to investigate the total energy electricity usage based on different types of shopping mall design layout while understanding the awareness of end user toward the building characterizes pertinent to energy uses of shopping malls. This research was conducted at two low-rise shopping malls of AEON AU2 and AEON Alpha Angle in Klang Valley. The field study was conducted to explore the building configuration including the size, building form, orientation and opening. The data were collected and analyzed in order to have better understanding of total energy usage in these case studies. The Building Energy Index (BEI) in the case studies was calculated and the results are be compared. The results of study find that the BEI for open building has lower value than enclosed building.